The dose–response relationship between smoking and the risk factor for invasive pulmonary aspergillosis in patients with severe fever with thrombocytopenia syndrome - Dai, Yan; Pu, Qinqin; Hu, Nannan; Zhu, Jin; Han, Yaping; Shi, Ping; Li, Jun; Jin, Ke (Frontiers in Microbiology, 2023)
Objectives: Invasive pulmonary aspergillosis (IPA) widely developes in immuno-compromised people, and a high incidence of IPA has been observed in patients with severe fever with thrombocytopenia syndrome (SFTS). Our study aimed to determine the independent risk factors of IPA and the relationship between smoking status and the risk of IPA in SFTS patients. Methods: A retrospective analysis of SFTS patients in the First Affiliated Hospital of Nanjing Medical University from May 2011 to December 2021 was reviewed. All the patients were divided into IPA and non-IPA group. We compared the demographic characteristics, clinical manifestation, laboratory parameters, treatment and prognosis, and explored the risk factors of IPA by logistic regression and ROC curve. The dose-dependent effect of smoking on risk of IPA was further estimated, including the age of smoking initiation, daily smoking amount, smoking duration, and pack-years of smoking. Results: In total, 189 individuals were included. Compared with the non-IPA group, the IPA group had higher levels of smoking, drinking, cough, dyspnea, aCCI scores, Dabie bandavirus (DBV) RNA load, ferritin, PCT, IL-6, APTT, LDH, BUN, creatinine, lower levels of FT4 and TSH. The incidence of MODS, admission to ICU, ventilation and broad-spectrum antibiotic treatment were significantly higher in IPA group than in non-IPA group. Multivariable logistic analysis showed that smoking history, cough, creatinine, the admission to ICU, broad-spectrum and corticosteroid therapies were the independent risk factors for IPA in SFTS patients. We further confirmed that the age of smoking initiation less than 30 years, smoking at least one pack per day, smoking at least 40 years, and with at least 40 pack-years of smoking exposure were the independent risk factors of IPA in smokers. Conclusions: The prognosis of SFTS patients with IPA is worse than non-IPA. Attention should be paid to SFTS patients with smoking history, cough, creatinine, the admission to ICU, broad-spectrum and corticosteroid therapies. There is a strong dose-dependent association between smoking and IPA development in SFTS patients. Prophylactic antifungal therapy should be considered for SFTS patients with these risk factors, but further studies are necessary to determine if it is beneficial for the prognosis of these patients.